A prospective analysis evaluating tissue biopsy location and its clinical relevance in chronic rhinosinusitis with nasal polyps. Issue 11 (1st September 2017) - Weibman, Ava R.; Huang, Julia He; Stevens, Whitney W.; Suh, Lydia A.; Price, Caroline P.E.; Lidder, Alcina K.; Conley, David B.; Welch, Kevin C.; Shintani‐Smith, Stephanie; Peters, Anju T.; Grammer, Leslie C.; Kato, Atsushi; et al.
Abstract : Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) has a high propensity for recurrence. Studies suggest that eosinophilia influences disease severity and surgical outcomes, but the selection of sinonasal site for measuring eosinophilia has not been examined. The aim of this study was to investigate how region‐specific tissue eosinophilia affects radiographic severity, comorbidity prevalence, and polyp recurrence risk following sinus surgery. Methods: Eosinophil cationic protein (ECP) levels in uncinate tissue (UT) and nasal polyp (NP) homogenates from 116 CRSwNP patients were measured using enzyme‐linked immunosorbent assay (ELISA). Clinical history, radiographic severity, and time to polyp recurrence were obtained from electronic health records. The correlations between baseline Lund‐Mackay scores and comorbidities were compared between UT and NP ECP levels. Cox regression and Kaplan‐Meier analysis were then performed to assess whether UT or NP ECP better predicted recurrence. Censoring occurred at 4 years or at last follow‐up if there was no endoscopic diagnosis of recurrent polyps. Results: Lund‐Mackay scores were significantly correlated with UT and NP ECP ( r = 0.46 and 0.26 respectively, p < 0.05). UT but not NP ECP was significantly higher in patients with asthma ( p < 0.01) and aspirin‐exacerbated respiratory disease (AERD) ( p < 0.05). Polyp recurrence risk was only significantly higher for patients with eosinophilic UT tissue (hazard ratio [HR] = 2.84, p = 0.025). When measured in NP, eosinophilia did not predict recurrence. Conclusion: Although ECP in NP was higher than in UT tissue, eosinophilia in UT tissue was a more clinically coherent biomarker of baseline radiographic severity, comorbid asthma and AERD, and prospective polyp recurrence risk than NP eosinophilia.